Dahil mahal kita the Dolzura Cortes story
Dolzura and Paolo met at pizza parlor where she works. Paolo and Dolzura become friends, at that night they made love Dolzura thought Paolo will be his shining Armour, but she was wrong for Paolo never bothered to see her again. Because of this, Dolzura accepted the proposal of her Australian suitor Keith. Dolzura handle their business (night club) and sometimes she go out with customers. For years, Dolzura found out she was infected with AIDS...